2022
DOI: 10.3389/fnbeh.2022.923732
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transposable Elements in Sexual Development

Abstract: Up to 50% of most mammalian genomes are made up of transposable elements (TEs) that have the potential to mobilize around the genome. Despite this prevalence, research on TEs is only beginning to gain traction within the field of neuroscience. While TEs have long been regarded as “junk” or parasitic DNA, it has become evident that they are adaptive DNA and RNA regulatory elements. In addition to their vital role in normal development, TEs can also interact with steroid receptors, which are key elements to sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 152 publications
(252 reference statements)
0
2
0
Order By: Relevance
“…Scholars propose that MORC3 may play a role in gonadal development. Desai et al (2021) found that MORC3 may be involved in chromatin compaction to silence transposable elements ( TEs ), thus regulating gonadal differentiation and gene expression related to gonadal development ( Chiang et al, 2022 ). MORC3 is important for the transcription of P-element-induced wimpy testis ( PIWI )-interacting-RNA ( piRNA ) precursors and subsequently affects piRNA production and that the piRNA pathway plays a crucial role in the suppression of TE by the de novo methylation of DNA in mouse embryonic male germ cells ( Kojima-Kita et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars propose that MORC3 may play a role in gonadal development. Desai et al (2021) found that MORC3 may be involved in chromatin compaction to silence transposable elements ( TEs ), thus regulating gonadal differentiation and gene expression related to gonadal development ( Chiang et al, 2022 ). MORC3 is important for the transcription of P-element-induced wimpy testis ( PIWI )-interacting-RNA ( piRNA ) precursors and subsequently affects piRNA production and that the piRNA pathway plays a crucial role in the suppression of TE by the de novo methylation of DNA in mouse embryonic male germ cells ( Kojima-Kita et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations led Sarachana et al, (2011) to suggest that a decrease in RORA and its transcriptional target aromatase may be related to the reported elevated testosterone in amniotic fluid associated with ASD traits, which has been proposed as a factor influencing the male sex bias in ASD [ 43 ]. Sex differences in TEs in the human genome may be related to the biology of sex differences, such as higher TE density on the Y chromosome, differences in DNA methylation regulators (DNA methyltransferase enzymes and methylcytosine dioxygenases; TET), and histone modification marks [ 44 ]. Another interesting TF is vitamin D receptor (VDR), a nuclear receptor/steroid hormone receptor superfamily.…”
Section: Discussionmentioning
confidence: 99%